Evaluation of technological properties and safety indicators of poultry products made using natural marinades - Tischenko, Vasyl; Huba, Svitlana; Bozhko, Nataliia (Technology audit and production reserves, 2026)
The object of research is the technology and quality parameters of marinated semi-finished poultry meat products using marinades based on cherry juice of the Chernokorka variety (Cherry tree Chernokorka) and Josta berries (Josta). The problem solved in the research is the lack of an exhaustive definition of the influence of natural marinades on the complex of indicators of natural semi-finished poultry meat products. The key evaluation parameters were: color, pH, moisture retention capacity, marinade absorption, losses during heat treatment, sensory indicators, safety indicators of finished products. The process of passive marinating (soaking) was carried out for 12 hours. For this, chicken breasts were soaked in marinade solutions No. 1 (josta berry juice: purified water: sea salt – 60:37:3) and No. 2 (cherry berry juice: purified water: sea salt – 60:37:3). As a control, samples were marinated in marinades of the company Spice Land LLC (Ukraine). It was found that the juice of josta berries differs from cherry juice in a higher content of total phenolic compounds (327.16 versus 201.31 mg/100 ml) and a higher titrated acidity (3.5%). The antioxidant activity of josta juice is at a high level: juice polyphenols inhibit 97.41 ± 1.57% of the DPPH free radical. An increase in moisture content was determined in products marinated with cherry juice (76.21%) and josta juice (77.16%). The use of cherry and josta juice in marinades accelerates their diffusion into muscle tissue. The highest sorption capacity was found in samples treated with marinade with josta juice (1.43%), which is 1.5 times higher than the control. The use of berry juices in marinades reduces thermal losses by 2.17–2.68%. It has been proven that the use of cherry and josta juice as bases for marinades in the technology of semi-finished poultry meat products improves the taste and aroma profile of finished products, inhibits oxidative processes in marinated semi-finished poultry meat products, and ensures their microbiological safety during storage.